Topological methods in the theory of operator inclusions in Banach spaces. I - Mel'nik, V. S. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
We develop topological methods for the investigation of operator inclusions in Banach spaces, prove the generalized Ky Fan inequality, and study the critical points of many-valued mappings in topological spaces.